Analisis Beberapa Sifat Fisika dan Kimia Tanah pada Lahan yang Berbeda di Desa Lasori Kecamatan Mawasangka Timur Kabupaten Buton Tengah - Azidun, Azidun; Ginting, Sahta; Resman, Resman; Darwis, Darwis; Alam, Syamsul; Namria, Namria (Agritechpedia, 2023)
This study aims to determine some of the physical and chemical properties of the soil on different lands in Lasori village Mawasangka Timur district cental Buton District. Soil samples were analyzed at the UPT. University integrated laboratory halu oleo. This research is a descriptive study using the observation method, namely taking samples in the field and analyzing them in thelaboratory to obtion quantitative data. Point determination is carried out using a random method sampling. The land used is a corn sample point and cassava sample point. There were 6 sample units from different land to represent 1 land. The results showed that the physical and chemical properties of the soil on different land in Lasori village Mawasangka Timur District central Buton Tengah. The parameter were very high that becomes the limiting factor for physical properties is bulk density with 1,00 g/m3 – 1,36g/m3 with low – medium criteria. The soil textures are dusty loam and sandy loam. Porosity with 48.12% - 62,18%, diamond not good. While limiting the factor for chemical properties is soil pH with a value of 6,38 – 7,68, a dlighty acidic to slightly alkaline content of C-organic with a vaule of 2,27% - 5,28% moderate-high index and KTK with a value of 35,26 me/100g – 58,36 me/100g with a high – very high index. Keywords: Soil physical, corn, soil chemical, cassava.